Realization of TCP Syn Flood Attacks using the Kali Linux - Vuletić, Dejan V.; Nojković, Nemanja D. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Denial-of-Service (DoS) is a type of attack that attempts to prevent legitimate users from accessing network services. This is accomplished by overloading network services or by excessive connectivity, causing a drop in a connection or a service. DoS tools are designed to send large numbers of requests to the targeted server (usually web, FTP, e-mail server), in order to overwhelm server resources and make it unusable. There are various ways in which attackers achieve this. One of the usual ways is simply overwhelming the server by sending too many requests. This will disable the normal functioning of the server (and the web pages will open more slowly), and in some cases it can lead to a situation that the server ceases to operate. This paper shows some effects of TCP Syn Flood Attacks (using Kali Linux) through the change of processor utilization and the unavailability of the target computer (executing ping command).